Nurses' Burnout: The Influence of Leader Empowering Behaviors, Work Conditions, and Demographic Traits - Rola H. Mudallal PhD, RN; Wafa'a M. Othman MSN; Nahid F. Al Hassan MSN (SAGE Publishing, 2017)
Nurse burnout is a widespread phenomenon characterized by a reduction in nurses' energy that manifests in emotional exhaustion, lack of motivation, and feelings of frustration and may lead to reductions in work efficacy. This study was conducted to assess the level of burnout among Jordanian nurses and to investigate the influence of leader empowering behaviors (LEBs) on nurses' feelings of burnout in an endeavor to improve nursing work outcomes. A cross-sectional and correlational design was used. Leader Empowering Behaviors Scale and the Maslach Burnout Inventory (MBI) were employed to collect data from 407 registered nurses, recruited from 11 hospitals in Jordan. The Jordanian nurses exhibited high levels of burnout as demonstrated by their high scores for Emotional Exhaustion (EE) and Depersonalization (DP) and moderate scores for Personal Accomplishment (PA). Factors related to work conditions, nurses' demographic traits, and LEBs were significantly correlated with the burnout categories. A stepwise regression model-exposed 4 factors predicted EE: hospital type, nurses' work shift, providing autonomy, and fostering participation in decision making. Gender, fostering participation in decision making, and department type were responsible for 5.9% of the DP variance, whereas facilitating goal attainment and nursing experience accounted for 8.3% of the PA variance. This study highlights the importance of the role of nurse leaders in improving work conditions and empowering and motivating nurses to decrease nurses' feelings of burnout, reduce turnover rates, and improve the quality of nursing care.